PENDEKATAN TEKNOLOGI DALAM PERENCANAAN DESAIN PEMBELAJARAN - Atnawi, Atnawi (Universitas Islam Madura, 2016)
Design development of learning is one alternative to improve the quality of education that can be done by education practitioners for the progress and development of civilization of a nation, therefore, a teacher who serves as an agent of transfer of knowledge has a role that is very urgent in order to channel their knowledge to learners, through kapabiltas and skill, teachers are required to print a better generation that will have an impact on the advancement of a civilization. Therefore, it is necessary for every teacher to know and master the subject, purpose and characteristics of each of their students, so that the learning process runs effectively and efficiently as well as the lessons learned can be run properly and in accordance with the wishes of teachers and learners. The last stage is necessary diperlu considered by every teacher or teacher is the evaluation of learning activities that had been running and is already in its path, it is intended to be used as initial foundation for the progress and development of education in the future, which in this stage is equally important as the stage next because the evaluation is to determine the parts and know every student's ability in terms of both science and from the other, so that a teacher can separate and define the level of difficulty according to the lessons yamg ability possessed by each individual participant students and the learning process does not end there vain and walked with efektik.